Peningkatan Kualitas Aplikasi Pemantau Media Sosial dan Media Daring Menggunakan Metode WebQEM - Condro Kartiko; Galuh Boy Hertantyo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Along with the rapid growing world of technology nowadays, application becomes an important requirement for every human in person. Human becomes dependent on variety of applications, ranging from small scale application for entertaining user to large scale web application for one or multiple businesses work. In this research the application that used is social and online media monitoring at PT. XYZ in Indonesia. Based on this case, a software quality testing is needed so a software can be said worthy and qualified to use, not just limited to mere testing, but also for optimizing the software to create a well maintained application in accordance with software development life cycle. In this paper, WebQEM is used in optimization for web application. There are two kinds of evaluations: basic evaluation and global evaluation. First global evaluation of monitoring social media and online media application gives a score of 70,44%. After evaluation, an improvement is applied to the application according to the criteria from the result of first global evaluation. Second global evaluation gives a value of 77,41%, from the improvement in first global evaluation. This proves that WebQEM method for optimization of monitoring social media and online media application can improve the software quality.